Revisão sistemática da literatura com Bibliometrix sobre forças de adesão de nanopartículas - Silva, Karen Laiz da (Universidade Federal de São Carlos, 2022)
This work is a systematic review of the literature that aims to elucidate the roots of knowledge about adhesion forces between nanoparticles and surfaces, given the strong relationship between this topic and air filtration. Filters with a biocidal effect are essential for human health, taking as an example air conditioning filters and masks whose importance was highlighted by the Covid-19 pandemic. The articles analyzed were selected from SCOPUS and Web Of Science databases. The search was refined through the application of the functions of the Bibliometrix package, an open-source tool in R language, aimed to systematic analysis of the literature. Bibliometric aspects of the articles obtained by the searches were analyzed, such as repetition and correlation of keywords, division of works into sets that contained common concepts and authors' productivity and relevance. The main references cited among the documents selected at the end of the bibliometric analysis were gathered. Those whose theme coincided with the proposal of the present work were selected. The quality of such studies was evaluated based on the impact factor of the journals in which they were published, considering that this would be a way of guaranteeing that only works that had followed scientific accuracy throughout their execution were read and compiled. The referenced works were extracted from the CAPES Web Of Science portal, read and analyzed. Impact aspects of such publications were considered, based on the number of citations and impact factor of the journals in which the works were published. The most used keywords and the research centers to which the authors were affiliated were analyzed. The functioning of Atomic Force Microscopy (AFM) was described, which still remains the main method used to measure force versus distance curves and determine the Hamaker's constant. The theoretical models of Hamaker, Rumpf and Rabinovich were explored, in order to bring more robustness to the concept of adhesion force, in order to contribute to the research of the Environmental Control laboratory at UFSCar, in the scope of membranes for air filtration.
Systematic review of the literature with Bibliometrix on nanoparticle adhesion forces
Keywords: Forças de adesão; Nanopartículas; Revisão sistemática; Adhesion forces; Nanoparticles; Systematic review; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA